Multi-scale numerical analysis of flow and heat transfer for a parabolic trough collector. (March 2017) - Tang, Zhen; Zhao, Xin-Peng; Li, Zeng-Yao; Tao, Wen-Quan
Highlights: A fully coupled algorithm for the heat transfer in a PTC is presented. Effects of gas pressure, coating emissivity and envelope diameter are analyzed. An operation scheme of HTF speed to reduce the PTC total length is proposed. Abstract: This paper numerically investigated the coupled flow and heat transfer of a parabolic trough collector (PTC), with the non-uniform heat flux boundary condition on the absorber wall and the rarefied gas effects in the annular vacuum gap being taken into consideration. A fully coupled cross-sectional heat transfer model is established with Direct Simulation Monte Carlo (DSMC) method for the rarefied gas flow and heat transfer in the vacuum annual gap. The PTC tube efficiency can be obtained from the above simulation for a given HTF temperature. Such simulation is conducted for several specified HTF temperature and different efficiency data are obtained. These data are fitted by an equation. This equation is then used to advance the HTF temperature in the axial direction. In such a way a simplified 3D model for the design of a PTC receiver is obtained. Cross-sectional simulation results show that when the gas pressure is less than 0.1 Pa further decrease in pressure makes no further contribution to reduce the heat loss. The effects of periphery non-uniform distribution of heat flux, coating material emissivity, envelope diameter and HTF inlet velocity on the PTC efficiency are discussed. An operation variant is proposed by using the 3D model by which the total PTC tube length can be reduced for a given thermal load.